Performance Comparison Between FEDERICA Hand and LARM Hand. (14th July 2015) - Carbone, Giuseppe; Rossi, Cesare; Savino, Sergio
This paper describes two robotic hands that have been developed at University Federico II of Naples and at the University of Cassino. FEDERICA Hand and LARM Hand are described in terms of design and operational features. In particular, careful attention is paid to the differences between the above-mentioned hands in terms of transmission systems. FEDERICA Hand uses tendons and pulleys to drive phalanxes, while LARM Hand uses cross four-bar linkages. Results of experimental tests are reported to show how key design issues affect each robotic hand's performance.